2009
DOI: 10.1074/jbc.m805787200
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis Mediates Overexpression of Antizyme Inhibitor Resulting in Increased Polyamine Levels and Apoptosis in Alveolar Macrophages

Abstract: Pneumocystis pneumonia (PcP) is the most common opportunistic disease in immunocompromised patients. Alveolar macrophages are responsible for the clearance of Pneumocystis organisms; however, they undergo a high rate of apoptosis during PcP due to increased intracellular polyamine levels. In this study, the sources of polyamines and mechanisms of polyamine increase and polyamine-induced apoptosis were investigated. The level of ornithine decarboxylase (ODC) was elevated in alveolar macrophages, and the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…Viability of the organisms was also not a factor in altering calmodulin mRNA levels; therefore, the molecule(s) responsible for downregulating the expression of calmodulin may be a soluble factor(s) from the host or organism. Previous reports have implicated ␤-glucan (15, 37), the major surface glycoprotein (6,34), and polyamines from the organism (35,37) in modulation of host cell functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viability of the organisms was also not a factor in altering calmodulin mRNA levels; therefore, the molecule(s) responsible for downregulating the expression of calmodulin may be a soluble factor(s) from the host or organism. Previous reports have implicated ␤-glucan (15, 37), the major surface glycoprotein (6,34), and polyamines from the organism (35,37) in modulation of host cell functions.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Amø renders animals susceptible to Pneumocystis pneumonia (Pcp) (47), while increased Amø numbers retard progression of the disease (33; M. E. Lasbury submitted for publication). Low Amø numbers in animals with Pcp are caused by increased apoptosis, which is related to the catabolism of intracellular polyamines and production of hydrogen peroxide (35,37). Reduced survival pathway signaling and antioxidant expression also contribute to the apoptosis of Amø during Pcp (Lasbury, submitted).…”
mentioning
confidence: 99%
“…In a surprising revelation, recent studies have identified significant AM apoptosis during P. murina infection (13) that appears to be mediated by immune cell polyamine and peroxide production (14). Mechanistic studies demonstrated that the observed AM apoptosis was a result of Pneumocystis organisms inducing antizyme inhibitor overexpression in AMs, leading to increased polyamine synthesis and uptake (15).…”
mentioning
confidence: 99%
“…Although alveolar macrophages (AMs) play an important role in the clearance of microorganisms in the lungs, they are defective in phagocytosis (1,2), and their number is decreased during PcP (3)(4)(5)(6)(7)(8). A cause of this AM number decrease is increased apoptosis due to elevated levels of intracellular polyamines (9,10). The causes for AM dysfunction during PcP are not clear; one possible cause is downregulation of the transcription factor PU.1 (11), as it regulates the expression of many macrophage receptors (11)(12)(13)(14)(15).…”
mentioning
confidence: 99%